Predictors of High-grade Vesicoureteral Reflux in Children with Febrile Urinary Tract Infections - Eom Ji Choi; Min Ju Lee; Sin-Ae Park; Oh-Kyung Lee (Korean Society of Pediatric Nephrology, 2017)
Purpose This study aimed to investigate clinical and radiological factors that may predict high-grade vesicoureteral reflux (VUR) in patients with febrile urinary tract infection (UTI). Methods We retrospectively analyzed medical records of 446 patients diagnosed with febrile UTI from March 2008 to February 2017. All patients underwent renal-bladder ultrasonography (RBUS), 99mTc dimercaptosuccinic acid (DMSA) renal scan, and voiding cystourethrography (VCUG), and were divided in to 3 groups: a high-grade VUR group (n=53), a low-grade VUR group (n=28), and a group without VUR (n=365). Results The recurrence and non-Escherichia coli infection rates in febrile UTI were significantly higher in the high-grade VUR group than in the other two groups (P<0.05). RBUS showed that hydronephrosis and ureter dilatation were more frequent in the high-grade VUR group than in the other groups (P<0.05). In the high-grade VUR group, a renal cortical defect was more likely to appear as multiple defects, and the difference in bilateral renal scan uptake between both kidneys was larger than in the other two groups (P<0.001). Conclusion Recurrent UTI, non-E. coli UTI, abnormal findings on RBUS such as hydronephrosis and ureter dilatation, and abnormal findings in the DMSA renal scan such as multiple renal cortical defects and greater uptake difference were associated with high-grade VUR. VCUG should be selectively performed when RBUS and/or DMSA renal scan reveal significant abnormalities.